2013
DOI: 10.1111/j.1365-4632.2012.05758.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Kaposi's sarcoma: a review and update

Abstract: Kaposi's sarcoma (KS) is an important mucocutaneous neoplasm with four well-known clinicopathologic types. Involvement of the oral cavity may be seen in all variants but is most common with AIDS-KS. The latter may signal undiagnosed HIV infection. Its common association with disseminated disease has potentially important diagnostic and therapeutic implications. Oral KS (OKS) most often affects the hard and soft palate, gingiva, and dorsal tongue with plaques or tumors of coloration ranging from non-pigmented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 41 publications
0
62
0
4
Order By: Relevance
“…Kaposi sarcoma (KS) is a mucocutaneous neoplasm of endothelial cell origin caused by the Kaposi sarcoma‐associated herpesvirus (KSHV or HHV8), which presents with four well‐known clinicopathologic subtypes. Involvement of the oral cavity may be seen in all subtypes, but most commonly in patients with the acquired immunodeficiency syndrome (AIDS)‐related form . Clinically, KS is characterized by brownish‐red to bluish purple lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaposi sarcoma (KS) is a mucocutaneous neoplasm of endothelial cell origin caused by the Kaposi sarcoma‐associated herpesvirus (KSHV or HHV8), which presents with four well‐known clinicopathologic subtypes. Involvement of the oral cavity may be seen in all subtypes, but most commonly in patients with the acquired immunodeficiency syndrome (AIDS)‐related form . Clinically, KS is characterized by brownish‐red to bluish purple lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, KS is characterized by brownish‐red to bluish purple lesions. This appearance is due to red blood cell extravasation and local deposition of hemosiderin within the tumor . Indeed, KS is a highly angiogenic neoplasm with dense and irregularly shaped, leaky blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Fatahzadeh and associates reported that dose reduction and modification of immunosuppression protocols after Kaposi sarcoma facilitated acute allograft rejection. 8 In a different study, excessive reduction or withdrawal of immunosuppression after the development of Kaposi sarcoma yielded to a statistically significantly increased risk of graft loss. 9 Similarly, in an observational study, 2 of 11 patients with nonmetastatic cancer lost their grafts due to chronic rejection after conversion to sirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Oral KS can involve the palate, tongue, gingiva, uvula and oropharynx as purple macules, patches, plaques, nodules or exophytic masses 2. Cutaneous KS can present as purplish, reddish, brown or black macules, plaques or nodules.…”
Section: Descriptionmentioning
confidence: 99%